Pemetaan Penggunaan Teknologi Informasi dan Komunikasi pada Lembaga-Lembaga di Lingkungan Pondok Pesantren Nurul Jadid Paiton Probolinggo - Karim, Abdul; ZR, Moch Ridho; Izzulhaq, Moh. Agung; Romadon, Moh. Wahyu; Rizky, Muhammad; Azizi, Moh. Rusli (Universitas Nurul Jadid, 2021)
This research is a mapping of the use of Information and Communication Technology (ICT) in the learning process at the educational unit of the Nurul Jadid Islamic Boarding School Paiton Probolinggo. The method used in this research is a mixed method with a case study approach. The method used to obtain data in the study was 1) a questionnaire. That is the method of collecting data by giving a set of questions or statements in writing to the respondents to be answered. This study took the object of research at the institution or formal education unit under the auspices of the Nurul Jadid Paiton Islamic Boarding School, Probolinggo, East Java. The object of this research is a formal institution from the junior secondary level to the upper secondary level. The results showed that the average use of Information and Communication Technology (ICT) in educational institutions under the auspices of the Nurul Jadid Islamic Boarding School in Paiton Probolinggo based on the recapitulation results was very good.